Letters of a Ticonderoga farmer, selections from the correspondence of William H. Cook and his wife with their son, Joseph Cook, 1851-1885 - Cook, William Henry, 1812-1885 (Ithaca, N.Y. : Cornell University Press, 1946., 1946)
xii, 134 pages : including frontispiece (facsimile) ; 22 cm